2014
DOI: 10.1093/infdis/jiu299
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostaglandin F2α Production in Lipid Bodies From Leishmania infantum chagasi: Insights on Virulence

Abstract: Lipid bodies (LB; lipid droplets) are cytoplasmic organelles involved in lipid metabolism. Mammalian LBs display an important role in host-pathogen interactions, but the role of parasite LBs in biosynthesis of prostaglandin F2α (PGF2α) has not been investigated. We report herein that LBs increased in abundance during development of Leishmania infantum chagasi to a virulent metacyclic stage, as did the expression of PGF2α synthase (PGFS). The amount of parasite LBs and PGF2α were modulated by exogenous arachido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(102 citation statements)
references
References 43 publications
8
93
1
Order By: Relevance
“…The inhibition of enzymes from the lipid mediators pathways has been widely used to efficiently control inflammatory responses31 as well as Leishmania infection burden32. In our experimental model, we found that treatment with an inhibitor of 15-lypoxigenase resulted in a reduction of RvD1 production, which mirrored a decrease in intracellular parasite viability.…”
Section: Discussionmentioning
confidence: 61%
“…The inhibition of enzymes from the lipid mediators pathways has been widely used to efficiently control inflammatory responses31 as well as Leishmania infection burden32. In our experimental model, we found that treatment with an inhibitor of 15-lypoxigenase resulted in a reduction of RvD1 production, which mirrored a decrease in intracellular parasite viability.…”
Section: Discussionmentioning
confidence: 61%
“…It is known that PGE 2 possesses anti-inflammatory activity, facilitating Leishmania infection in macrophages, suppressing inflammatory response in both cutaneous and visceral leishmaniasis [9194]. Moreover, reinforcing the context of a beneficial effect of PGE 2 for Leishmania survival, it was demonstrated that several Leishmania species possess lipid corpuscles as organelles and L. infantum is able to produce and release PGs, such as PGF 2α itself [95, 96] (Fig. 1d).…”
Section: Reviewmentioning
confidence: 89%
“…Inhibition of ATGL, genetically or pharmacologically, also impairs eicosanoid release in other types of immune cells, such as neutrophils [79]. In the intracellular parasites Leishmania and Trypanosoma , LDs can also act as a source of immunomodulatory prostaglandins implicated in improving the survival of the parasite within its host [80, 81]. The available evidence suggests that the enzymatically released AA is locally metabolized, as both eicosanoid precursors and eicosanoid producing enzymes have been found associated with LDs [75].…”
Section: 12 Storage Of Vitamins and Signaling Precursorsmentioning
confidence: 99%